2022
DOI: 10.18506/anemon.1003074
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Primary School Mathematics Pre-Service Teachers’ Scores in Calculus-I Course According to the Updated Curriculum: The Case of Derivative Concept

Abstract: This study aims to examine the change in pre-service teachers’ Calculus-I course passing scores in the undergraduate curriculum of primary school mathematics teaching program through comparing the previous curriculum and the new curriculum updated in 2018. This study is a causal comparison study, as it aims to compare the existing differences. The study group of the research consists of 212 pre-service teachers in primary school mathematics education department at a state university in the Aegean region, Turke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In the research depending on the sample of the Analysis 1 course, Erol et al (2022) revealed that students studying according to the previous curriculum were more successful in the subject of derivative. They considered that the main reason for this case was to have higher course hours.…”
Section: Kaynakçamentioning
confidence: 99%
“…In the research depending on the sample of the Analysis 1 course, Erol et al (2022) revealed that students studying according to the previous curriculum were more successful in the subject of derivative. They considered that the main reason for this case was to have higher course hours.…”
Section: Kaynakçamentioning
confidence: 99%